Evaluasi Kualitas Sistem Informasi Proyek Akhir menggunakan Effectiveness dan Satisfaction Quality in Use - Yuli Fitrisia; Mardhiah Fadhli (Ikatan Ahli Informatika Indonesia (IAII), 2019)
Information system Final Project Politeknik Caltex Riau has been built since 2015. However, this system has not been evaluated in terms of software quality. So that the problems that occur are not in accordance with the needs and user satisfaction. Software quality evaluation by user can be done by implementing an internationall standard model, one of which is ISO 9126-4 quality in use section. This quality model has four characteristics, namely Effectiveness, Productivity, Safety and Satisfaction. In this study two aspects of quality were raised, namely effectiveness and satisfaction. The implementation of these two quality aspects is by applying metric quality in use. The results of the evaluation of effectiveness can be concluded that the level of effectiveness of this system is good, especially for level of correctness of the output system is 100% and the error rate made by the user is 0%. Whereas the level of task that can be completed is>= 89%. And the results of quality satisfaction factors using satisfaction scale metrics can be concluded that the PA management system meets the satisfaction aspects for users. This is according to the results of the user's response to the statement on the questionnaire.